Pengaruh Modal, Tenaga Kerja Dan Teknologi Terhadap Produksi Industri Kerajinan Ukiran Kayu Di Kecamatan Ubud - Yuniartini, Ni Putu Sri (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 2, Februari 2013 (pp. 63-118), 2013)
The purpose of this study to determine whether there was an effect simultaneously and partially between capital, labor and technology for industrial production handicraft wood carving Ubud in Gianyar district. Samples are taken as much as 83 business units, with probability sampling methods, especially proportionate stratified random sampling. Data collected through observation, interviews and questionnaires. The analysis technique used is multiple linear regression. The results of data analysis showed simultaneous capital, labor and technology significant effect on industrial production handicraft wood carving in Ubud Gianyar district. Partially technology does not affect the production of wood carving handicraft industry, and labor sementaramodal positive and significant effect on the production of wood carving handicraft industry in Ubud Gianyar district. The government is expected to help the woodcraft industry was in terms of capital, labor maupunteknologi. This can be done by providing training, financial aid and help the marketing of wooden craft products of industry was that the industry can be developed which will boost the economy in particular and the District of Ubud Bali in general.
Keywords: capital , labor , technology , production